Recombinant Interleukin‐1 Receptor Antagonist Is an Effective First‐Line Treatment Strategy in New‐Onset Systemic Juvenile Idiopathic Arthritis, Irrespective of HLA‐DRB1 Background and IL1RN Variants - Erkens, Remco G. A.; Calis, Jorg J. A.; Verwoerd, Anouk; De Roock, Sytze; Ter Haar, Nienke M.; Den Engelsman, Gerda; Van der Veken, Lars T.; Ernst, Robert F.; Van Deutekom, Hanneke W. M.; Pickering, Alex; Scholman, Rianne C.; Jansen, Marc H. A.; et al. (Arthritis & rheumatology (Hoboken, N.J.), 2024)
Objective Human leukocyte antigen (HLA)‐DRB1*15:01 has been recently associated with interstitial lung disease (LD), eosinophilia, and drug reactions in systemic juvenile idiopathic arthritis (sJIA). Additionally, genetic variants in IL1RN have been linked to poor response to anakinra. We sought to reproduce these findings in a prospective cohort study of patients with new‐onset sJIA treated with anakinra as first‐line therapy. Methods HLA and IL1RN risk alleles were identified via whole‐genome sequencing. Treatment responses and complications were compared between carriers versus noncarriers. Results Seventeen of 65 patients (26%) carried HLA‐DRB1*15:01, comparable with the general population, and there was enrichment for HLA‐DRB1*11:01, a known risk locus for sJIA. The rates of clinical inactive disease (CID) at 6 months, 1 year, and 2 years were generally high, irrespective of HLA‐DRB1 or IL1RN variants, but significantly lower in carriers of an HLA‐DRB1*11:01 allele. One patient, an HLA‐DRB1*15:01 carrier, developed sJIA‐LD. Of the three patients with severe drug reactions to biologics, one carried HLA‐DRB1*15:01. The prevalence of eosinophilia did not significantly differ between HLA‐DRB1*15:01 carriers and noncarriers at disease onset (6.2% vs 14.9%, P = 0.67) nor after the start of anakinra (35.3% vs 37.5% in the first 2 years of disease). Conclusion We observed high rates of CID using anakinra as first‐line treatment irrespective of HLA‐DRB1 or IL1RN variants. Only one of the 17 HLA‐DRB1*15:01 carriers developed sJIA‐LD, and of the three patients with drug reactions to biologics, only one carried HLA‐DRB1*15:01. Although thorough monitoring for the development of drug hypersensitivity and refractory disease courses in sJIA, including sJIA‐LD, remains important, our data support the early start of biologic therapy in patients with new‐onset sJIA irrespective of HLA‐DRB1 background or IL1RN variants.